2016
DOI: 10.33762/bvetr.2016.124268
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Study of Ovine Q Fever in Basra Province ,Iraq

Abstract: Indirect ELISA test was used to detect specific antibodies against Coxiella burnetti in sheep in different regions of Basra province.184 local sheep breeds were randomly selected of different ages and of both sexes were used in this study, including 98 pregnant ewes, 55 non-pregnant ewes, 8 aborted ewes ,7 ewes of still births, moreover 112 lower than 2 years,more than 2 years 72and 13 rams.Results showed, that the percentage of infection detected by indirect ELISA were 41.84%.It have been concluded that C.bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The predisposition for infection in men may be explained by the protective role of female sex hormones (34). In sheep Out of 55 samples 21 (38.181%) were appeared infection with coxiellosis and this ratio agreed with the studies of (17)(18)(19)(20), where they explained and confirmed the zoonotic and worldwide distribution of this microorganism. This results consider the first one which confirms the present of infection in animal (sheep) in Al-Diwaniya city.…”
Section: Resultssupporting
confidence: 89%
“…The predisposition for infection in men may be explained by the protective role of female sex hormones (34). In sheep Out of 55 samples 21 (38.181%) were appeared infection with coxiellosis and this ratio agreed with the studies of (17)(18)(19)(20), where they explained and confirmed the zoonotic and worldwide distribution of this microorganism. This results consider the first one which confirms the present of infection in animal (sheep) in Al-Diwaniya city.…”
Section: Resultssupporting
confidence: 89%